Islam and Medicine: A Study on The Fatwa of Indonesian Ulama Council on Vaccines - Muslimin, JM.; Iskandar, Rizky Fauzi; Fatma, Yulia (Institut Agama Islam Negeri Curup, 2021)
The principles of Islamic jurisprudence can provide a convenient solution for practitioners of Islamic law in formulating the law of this rapidly expanding vaccine field for now and the future. This study aims to obtain the rationale of fiqhiyyah principles used by Indonesia Ulama Council (Majelis Ulama Indonesia, MUI) related to contemporary medical and health sciences, especially vaccines.. This research is a qualitative library research with primary source the fatwa ofÂ Indonesian Ulama Council.. The data and document are reviewed through content analysis techniques using descriptive-analytical and interpretative methods. The approach in this study uses the Principles of Islamic Jurisprudence (usul al-fiqh) and Islamic legal maxims (qawa'id fiqhiyyah) approach. . The conclusion of the study is the permissibility and prohibition of using vaccines are based on the ingredient of the vaccines. If the ingredient is extracted from allowed materials (halal), the vaccines are accepted. On the contrary, if it is contaminated by illegal materials, the vaccines are rejected. However, in the urgent situations, all vaccines can be accepted based on the logics of emergency and need.